PEMETAAN KEDALAMAN DAN POLA ARUS PASANG SURUT MUARA SUNGAI MASJID DUMAI - Musrifin ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2011)
Bathymetry and tidal pattern mapping have been conducted 2007.Observation intended to present a bathymetry and tidal pattern map. From the mapit could be found the place where sedimentation happened.The result showed that sedimentation in the mouth of Sungai Masjidestuary increasing by 0.75 meter/year. Type of tidal was mixed tide predominantlysemidiurnal. During the flood tide, direction of tidal current was from North to theSouth and then to South West. South West to North East and then to North duringebb tide.